CTNI-10. MAINTENANCE CHEMOTHERAPY USING BEVACIZUMAB FOR NEUROFIBROMATOSIS 2 PATIENTS WITH HEARING LOSS AND PROGRESSIVE VESTIBULAR SCHWANNOMAS: AN NF CLINICAL TRIALS CONSORTIUM STUDY (NF104). (9th November 2020) - Plotkin, Scott; Tonsgard, James; Ullrich, Nicole; Allen, Jeffrey; Blakeley, Jaishri; Dhall, Girish; Campian, Jian; Clapp, Wade; Fisher, Michael; Cutter, Gary; Korf, Bruce; Packer, Roger; et al.
Abstract: BACKGROUND: Bevacizumab treatment at 2.5–5 mg/kg/week is associated with hearing improvement and tumor shrinkage in about 40% of patients with neurofibromatosis 2 (NF2) and progressive vestibular schwannomas (VS). Treatment-emergent hypertension and proteinuria are common with prolonged treatment, and data supporting strategies to maintain hearing and minimize toxicity are lacking. METHODS: We conducted a multicenter, phase II, open-label study of bevacizumab for subjects (≥6 years old) with NF2, hearing loss, and progressive VS. After 6 months of induction therapy (10 mg/kg every 2 weeks), subjects received low dose bevacizumab at 5 mg/kg every 3 weeks during maintenance therapy (18 months). Hearing decline was defined as a significant decrease in word recognition score below baseline. Progressive disease was defined as ≥20% increase in tumor volume from baseline. RESULTS: Twenty of 22 subjects (median age=23 years) were treated with maintenance bevacizumab. The proportion of subjects free from hearing decline at 6, 12, and 18 months was 88%, 94%, and 85%, respectively; the proportion free from tumor progression at 6, 12, and 18 months from baseline was 88%, 94%, and 85%, respectively. Three subjects (15%) experienced hearing loss during maintenance and required dose escalation. Maintenance chemotherapy with bevacizumab was well tolerated: 1 subject discontinued due to perirectal abscess and 2 discontinued by choice. Grade 3 hypertension occurred in 2 subjects (10%). Adverse events of interest included hypertension (55%), proteinuria (20%), and irregular menstruation (6/13, 46%). CONCLUSIONS: Maintenance chemotherapy with bevacizumab at 5 mg/kg every 3 weeks is associated with prolonged hearing and tumor stability that surpasses historical controls. A minority of subjects require dose escalation during low dose bevacizumab treatment.